SUNDANESE ISOGLOSSES OF LEXICAL VARIATION IN KABUPATEN KUNINGAN - Fahmy Hygiewis, - (2008)
This paper entitled Sundanese Isoglosses of Lexical Variation in Kabupaten Kuningan, discussed the distribution of lexical variation in 32 districts of Kabupaten Kuningan. The study was conducted to uncover dialect maps in Kabupaten Kuningan, their isogloss lines, and also major lexical variations. The study employed descriptive design. The data were collected from 32 respondents by using two methods, questionnaire and interview. Each respondent represents one district of Kabupaten Kuningan. By using judgment sampling technique, the respondents were chosen. The data were analyzed in three ways: populating the data, mapping the data and describing the map. As the result, the study revealed 30 dialect maps in Kabupaten Kuningan. The maps described the distributions of 135 lexical variations and the isogloss lines. Based on the maps; it was also found that the isogloss lines were mostly overlapping. It means that, most of Kuningan people tend to use different lexical variations compared to their surrounding districts. Besides, it was also found that there were five major lexical variations used by the Kuningans.